Council of Europe - Sport
Sport brings people together. At its best, it contributes to their health and happiness, breaking down barriers and building trust and community spirit. For over five decades, the Council of Europe has advocated fair play and respect in sport, tackling corruption and helping make sport safe, ethical and accessible to all. This work contributes to the creation of inclusive, democratic societies which respect human rights and the rule of law - the Council of Europe`s raison d`être.